The human brain book - Aldridge, Susan.; Page, Martyn.; Parker, Steve, 1952- (DK Pub., 2009)
Combining the latest findings from the field of neuroscience with expert text and state-of-the-art illustrations, "The Human Brain Book" is a complete guide to the one organ in the body that makes each person a unique individual. Includes an interactive DVD.